Predictability of Spread of Epidural Anesthesia for Cesarean Section Using Incremental Doses of Lidocaine Hydrocarbonate with Epinephrine. Issue 3 (May 1989) - Gambling, David R.; Mcmorland, Graham H.; Mayson, Kelly; Moore, Randolph
Abstract : The relationship between patient height and total volume of lidocaine hydrocarbonate (1.73%) with epinephrine, required to produce epidural anesthesia for Cesarean section, was studied. Volume of local anesthetic, time to maximum block, highest segmental block, and number of spinal segments blocked were recorded. The segmental dose requirement (SDR) was calculated. All the results from 9 "short" (< 5′2″) and 18 "tall" (> 5′2″) patients were compared. There were no intergroup differences between any of the measured variables, and a scatterplot showed no linear relationship between patient height and the volume of the local anesthetic used. The mean values obtained for volume of local anesthetic used in both subgroups were compared with suggested arbitrary volumes of 25 ml for "tall" patients and 18 ml for "short" patients, used as a single-dose through an epidural needle. Using a one-sample hypothesis test, a significant difference was seen in tall patients (16.0 ± 2.9 v 25; p < .001), but not in the short subgroup (15.9 ± 3.2 v 18; p < .082). Patient height is a poor predictor of the volume of lidocaine hydrocarbonate required for epidural anesthesia in pregnant women. Selecting an arbitrary volume of local anaesthetic for use as a single epidural dose may result in either an excessively high or inadequate segmental block. Well-controlled titration of local anesthetic through an epidural catheter is recommended for elective Cesarean section.